Challenging the indiscriminate use of temozolomide in pediatric high‐grade gliomas: A review of past, current, and emerging therapies. Issue 1 (16th October 2019) - Guerra‐García, Pilar; Marshall, Lynley V.; Cockle, Julia V.; Ramachandran, Purushotham V.; Saran, Frank H.; Jones, Chris; Carceller, Fernando
Abstract: Pediatric high‐grade gliomas (pHGG) constitute 8% to 12% of primary brain tumors in childhood. The most widely utilized treatment encompasses surgical resection followed by focal radiotherapy and temozolomide. However, experiences over past decades have not demonstrated improved outcomes. pHGG have been classified into different molecular subgroups defined by mutations in histone 3, IDH gene, MAPK pathway, and others, thereby providing a rationale for various targeted therapies. Additionally, immunotherapy and drug repurposing have also become attractive adjunctive treatments. This review focuses on past, present, and emerging treatments for pHGG integrating molecular research with the mainstream pediatric drug development in Europe and the United States to sketch a way forward in the development of novel therapeutic approaches. The implementation of randomized clinical trials with adaptive designs, underpinned by a robust biological rationale, and harnessing collaboration between the pharmaceutical industry, academia, regulators and patients/parents organizations will be essential to improve the outcomes for these children.